Արվեստագետի եւ արվեստի քննադատի փոխհարաբերության մասին. երկու զուգահեռ հայ արվեստի պատմությունից - Ավագյան, Արմինե
The article trys to clarify the functions of an art critic in Armenian reality, as well as the relationship between the critic and the artist. The role of the art critic is observed in the contexte of the art creation: the question is how much the critic influences on the development of the artist. At the turn of 19-20th centuries the artists directed their activities towards the identification and evaluation of their cultural values. The first artist-critic relationship is discussed on the example of Karekin Hovsepian and Yeghishe Tadevosyan. This can be considered as cooperation. The other exemple is observed in the 60s of 20th century, in persons of Henrik Igityan and Minas Avetisyan. In this case too, we deal with cooperation rather than relationship. If Garegin Hovsepian and Yeghishe Tadevosyan aimed to preserve the nation, then Mians Avetisyan- Henrik Igityan cooperation aimed to overcome the social realism. В статье выясняются функций критика в армянской реальности, взоимоотношения между критиком и художником в период брожения искусствоведения как профессии. Обсуждается роль художественного критика с точки зрения создания искусства: до какой степени критик влияет на создание и развитие искусства художника? В конце XIX и в начале XX века художники и искусствоведы устремляли свои действия на идентификацию народных ценностей. Первое взоимоотношение между художником и критиком обсуждается на примере Гарегина Овсепяна и Егише Тадевосяна, что можно считать скорее сотрудничеством. Другой пример взоимоотношения прослеживается в 60-х годах 20-ого века, в лицах Генриха Игитяна и Минаса Аветисяна. В этом случае мы тоже имеем дело с сотрудничеством. Если сотрудничество между Гарегином Овсепяном и Егише Тадевосяном было направлено на сохранение народа, то сотрудничество между Минасом Аветисяном и Генрихом Игитяном было направлено на победу над социальным реализмом.
Keywords: Հայ արվեստի պատմություն